Językowe sposoby zbiorowego kreowania typów bohaterów w memach internetowych = Language means of the personal models` collective creating in Internet memes - Niekrewicz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to present the types of characters created by Internet users and an indication of language means used for characterisation of a person, resulting in restoration of stereotypical associations, perceptions and beliefs associated to life roles. The object of the analysis is language material derived from 14 000 internet memes published on two portals: Memy and Fabryka Memów.
Keywords: stereotypy; mem; gra werbalna; wspólnota internautów; stylizacja w języku potocznym; meme; language games; community of Internet users; styling in colloquial language